1986
DOI: 10.1007/bf00286224
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography in minor head injury in children

Abstract: EEG and CT scans of 280 cases of minor head injury in children under 15 years of age were studied. Abnormality on initial EEG was shown in 42.5%. Those who lost consciousness had a higher incidence of abnormality than those who did not, and it was higher between 4 and 13 years of age. The sleep state has much influence on the finding. The patients should be awake or in a light sleep stage. The most frequent abnormality was slow waves, seen predominantly in the occipital regions, and which tended to disappear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A predominance of slow waves was also reported by Enomoto, Ono, Nose, Maki and Tsukada (1986) from 280 cases of minor head-injured patients.…”
Section: Cognitive Tests and Eeg As Assessment Measures For Tbi And Addmentioning
confidence: 63%
“…A predominance of slow waves was also reported by Enomoto, Ono, Nose, Maki and Tsukada (1986) from 280 cases of minor head-injured patients.…”
Section: Cognitive Tests and Eeg As Assessment Measures For Tbi And Addmentioning
confidence: 63%
“…Early studies reported higher rates of EEG abnormality in subjects with post‐concussion syndrome (PCS); 13 however, these studies were often qualitative, had no modern radiologic information, lacked detailed analysis of paroxysmal activity (epileptic spike activity not associated with a major seizure), and included individuals outside the current definition of MTBI 14–16 . Other early studies did not demonstrate a higher incidence of abnormalities in the EEGs of MTBI patients than in the general population 17 .…”
Section: Discussionmentioning
confidence: 99%
“…23 There are also reports with either true epileptic seizures or partial seizurelike symptoms following minor closed head injury as well as epileptiform discharges in single cases. [24][25][26][27] In most studies, posttraumatic seizures developed within hours or days after the trauma, 26 and higher incidence of epilepsies were demonstrated mostly in moderate or severe head trauma. 28 However, in a population-based study, the incidence ratios for seizures even after mild head trauma was higher than expected with a standardized incidence ratio of 3.1 in children <1 year and 2.1 in children 1 to 4 years.…”
Section: Limitationsmentioning
confidence: 99%